Role of WhatsApp in improving L2 learner's communicative skills at intermediate level in the city of D. G. Khan - Hussain, Sabir (Revija za elementarno izobraževanje, 2025)
Learning English is difficult in all non-English speaking countries, including Pakistan, because learning another language after the mother tongue is difficult. This research aimed to improve L2 learners’ communication skills through WhatsApp. This research was experimental; sixty average scoring students were selected through pre-tests for this experiment; then, using the fishbowl random sampling technique, two groups, control and experimental, were formed with 30 students each. It was found that the students who were taught with the help of WhatsApp had excellent communication skills in L2 as compared to those students who were taught by traditional methods without WhatsApp.
Keywords: Angleščina; aplikacija WhatsApp; AV-aids; communicative skills; komunikacijske spretnosti; L2 learners; technology; tehnologija v izobraževanju; učenje angleščine kot tujega jezika; Učenje in poučevanje; WhatsApp; WhatsApp in communicative skills